Synthesis of Cembranoid Analogues through Ring‐Closing Metathesis of Terpenoid Precursors: A Challenge Regarding Ring‐Size Selectivity. Issue 35 (28th July 2015) - Heidt, Tanja; Baro, Angelika; Köhn, Andreas; Laschat, Sabine
Abstract: A systematic study on ring‐closing metathesis with Grubbs II catalyst to cembranoid macrocycles is described. Acyclic terpenoids with a functional group X in the homoallylic position relative to an RCM active terminus and substituents R, R 1 directly attached to the other terminal double bond were prepared from geraniol derived trienes and fragments that are based on bromoalkenes and dimethyl malonate. Such terpenoids were suitable precursors, despite the presence of competing double bonds in their framework. The size of R and R 1 is crucial for successful macrocyclization. Whereas small alkyl substituents at the double bond directed the RCM towards six‐membered ring formation, cross metathesis leading to dimers dominated for bulkier alkyl groups. A similar result was obtained for precursors without functional group X. In the case of unsymmetrically substituted terpenoid precursor (R=Et, R 1 =Me) with homoallylic OTBS or OMe group, the RCM could be controlled towards formation of macrocyclic cembranoids, which were isolated with excellent E ‐selectivity. The role of the substituents was further studied by quantum chemical calculations of simplified model substrates. Based on these results a mechanistic rationale is proposed. Abstract : Getting the right size : Macrocyclization of terpenoids with competing double bonds under Grubbs II catalysis requires a critical balance of steric effects to give cembranoid derivatives (see scheme), otherwise six‐membered ring formation or cross metathesis were favored. DFT calculations helped to explain the experimental results.